The Role of Distinct Subsets of Macrophages in the Pathogenesis of MS and the Impact of Different Therapeutic Agents on These Populations - Radandish, Maedeh; Khalilian, Parvin; Esmaeil, Nafiseh (Frontiers in Immunology, 2021)
Multiple sclerosis (MS) is a demyelinating inflammatory disorder of the central nervous system (CNS). Besides the vital role of T cells, other immune cells, including B cells, innate immune cells, and macrophages (MФs), also play a critical role in MS pathogenesis. Tissue-resident MФs in the brain’s parenchyma, known as microglia and monocyte-derived MФs, enter into the CNS following alterations in CNS homeostasis that induce inflammatory responses in MS. Although the neuroprotective and anti-inflammatory actions of monocyte-derived MФs and resident MФs are required to maintain CNS tolerance, they can release inflammatory cytokines and reactivate primed T cells during neuroinflammation. In the CNS of MS patients, elevated myeloid cells and activated MФs have been found and associated with demyelination and axonal loss. Thus, according to the role of MФs in neuroinflammation, they have attracted attention as a therapeutic target. Also, due to their different origin, location, and turnover, other strategies may require to target the various myeloid cell populations. Here we review the role of distinct subsets of MФs in the pathogenesis of MS and different therapeutic agents that target these cells.